Toxicological Monitoring of a Water Supply Reservoir by Acute Assays with Daphnia Pulex (2015)
ABSTRACT: Daphnia pulex assays (48 hours) were performed to determine acute toxicity of water samples from La Fe reservoir, Antioquia, Colombia. Eight sampling campaigns were done between March 2010 and June 2012, a period that included rainfall episodes. Samples were taken from the water column at three depths and from lotic areas. Physicochemical properties such as pH, electrical conductivity, temperature and dissolved oxygen were measured both in field and laboratory, and concentrations of dissolved iron (Fe), manganese (Mn), aluminium (Al), lead (Pb), cadmium (Cd) and chromium (Cr) were assessed. The overall results for the physicochemical properties remained at expected levels for natural waters with slightly higher conductivities in samples collected from bottom and some tributaries. The results of the toxicity tests showed significant mortalities in only 28% of assays. A higher mortality of Daphnia pulex was detected for tests performed during periods of higher precipitation (August 2010, February and July 2011) mainly for samples taken near the confluence of natural tributaries. No significant relationships between physicochemical variables and mortality of Daphnia pulex were found.